The Survivor as the Impossible Subject: Tracing Risk and Empowerment Discourse in Self-Defense Education - Mulholland, Kaylee (Women's studies in communication, 2025)
Content warning: Sexual violence and victim blaming. In this study, I engage my experiences conducting fieldwork as a survivor of sexual violence across two locations of an international self-defense organization. By tracing risk and empowerment discourses across fieldwork, informant interviews, and organizational documents, this study outlines a discursive slippage between risk prevention and victim blaming discourse. These discursive tensions highlight how the affective and temporal distancing associated with empowerment rhetorics is denied to survivors in self-defense education and constructs survivors as impossible subjects. As impossible subjects, survivors' experiences of violence form the very foundations of self-defense education while also being neglected within the space to control the distribution of risk and distance participants from violence.